2019
DOI: 10.1177/1475090219858810
|View full text |Cite
|
Sign up to set email alerts
|

Life-cycle assessment of ships: The effects of fuel consumption reduction and light displacement tonnage

Abstract: Life-cycle assessment has been widely applied in many industry sectors for years and there are some applications of this method in the shipping sector. Fuel consumption and material consumption are considered as crucial factors in the life cycle of ship. This study uses the life-cycle assessment method to show the effects of fuel consumption reduction and light displacement tonnage on the environmental performance of ships. This is done by comparing the environmental impacts of 25 investigated scenarios with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Generally, LCA studies are conducted in the ship operation phase (Dong and Cai, 2020;Hwang et al, 2020), while only a few studies are conducted in the manufacturing phase. The impact assessment results calculated based on the IMO regulations in the manufacturing phases are shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, LCA studies are conducted in the ship operation phase (Dong and Cai, 2020;Hwang et al, 2020), while only a few studies are conducted in the manufacturing phase. The impact assessment results calculated based on the IMO regulations in the manufacturing phases are shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hull form optimization using CFD and model testing has been at the core of research for many years. Finding optimum dimensions and hull shape ratios will significantly decrease resistance, therefore, cutting 10 % of the fuel consumption of a tanker [12]. The economy of scale stands for the increase of cargo transported per voyage; doubling the cargo capacity will only require increasing the power output and fuel consumption by two-thirds, therefore energy-efficiency per freight unit is increased [10].…”
Section: Fuel Consumption Reduction Strategiesmentioning
confidence: 99%
“…This research showed that the LNG supply chain would be sensitive to economic and environmental impacts of fuels. In addition, Dong and Cai [26] discussed several ways to reduce the environmental impact by reducing the fuel consumption rate.…”
Section: Literature Reviewmentioning
confidence: 99%